2013
DOI: 10.1097/sla.0b013e31827a0e82
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Alterations in the Roux-en-Y Gastric Bypass Recipients

Abstract: RYGB recipients have significantly shorter tmax for the studied orally administered medications, but otherwise no other significant changes in PK were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 46 publications
4
65
3
Order By: Relevance
“…Although the overall apparent oral clearance of midazolam was unchanged at the 3‐ and 12‐month visits after RYGB, peak concentrations were significantly higher at both postoperative time points. This finding differs from the results of another study that examined oral midazolam bioavailability after RYGB . Another study also reported that the T max of oral midazolam was decreased but did not find significant changes in C max or AUC.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Although the overall apparent oral clearance of midazolam was unchanged at the 3‐ and 12‐month visits after RYGB, peak concentrations were significantly higher at both postoperative time points. This finding differs from the results of another study that examined oral midazolam bioavailability after RYGB . Another study also reported that the T max of oral midazolam was decreased but did not find significant changes in C max or AUC.…”
Section: Discussioncontrasting
confidence: 93%
“…It compared the pharmacokinetics of midazolam in RYGB recipients with nonsurgical control subjects. Moreover, it collected fewer blood samples during the midazolam absorption phase and may have missed the actual T max and C max . Because midazolam was administered as an oral liquid in both studies, one would expect the time to reach C max to be within 10–15 minutes after drug administration in the postoperative patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed in a population pharmacokinetic (PK) analysis that plasma clearance (CL) of the cytochrome P450 3A (CYP3A) substrate midazolam is 1.7 times increased in patients after a weight loss procedure in comparison to morbidly obese patients, whereas oral bioavailability (F total ) was unaltered . Similar results have been reported before for RYGB patients in comparison with age, gender, and body mass index‐matched control patients . Although it is well known that CYP3A resides both in the gut and in the liver, these analyses that use total oral bioavailability (F total ) as parameter do not allow for a distinction between the contribution of presystemic gut and presystemic liver metabolism.…”
supporting
confidence: 78%
“…A subsequent matched cohort study from the same group showed that RYGB patients required higher doses of sedation during EGD than the non-RYGB with similar age, gender and BMI [31]. Authors hypothesized that these findings could be due to an improvement in liver function after gastric bypass, which resulted in an improvement in liver metabolism of fentanyl and midazolam, which subsequently led to increased requirement of both sedatives during EGD [3233]. …”
Section: Obesity and Sedationmentioning
confidence: 99%